2008
DOI: 10.1002/cyto.b.20383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications and availability of CD4+ T cell count testing in sub-Saharan Africa

Abstract: The absolute CD41 T cell count in adults and CD41 T cell percentage of lymphocytes (CD4%) in pediatrics compliment clinical history and physical examination to inform decisions about initiating antiretroviral therapy (ART). In addition, these immunologic markers predict host susceptibility to specific opportunistic infections, selected drug toxicities, and mortality. These benefits argue strongly for the availability of CD41 T cell testing capacity in all settings where HIV infection is treated. Several curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Thus, a person with a low CD4 T cell count may show relatively high TLC if high amounts of B cells are expressed due to immune hyperactivation from exposure to the wide variety of circulating antigens consequent on varieties opportunistic infections in HIV patients with severe immunosuppression. 4 Our previous study indicated that most HIV patients in our setting present late with a varieties of opportunistic infections. 19 We observed good correlation between TLC and CD4 count using the Spearman's rank test (r = 0.632) in HAART-experienced and r = 0.494 in HAARTnaïve cohorts, similar to the value of 0.431 reported by Akinola.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, a person with a low CD4 T cell count may show relatively high TLC if high amounts of B cells are expressed due to immune hyperactivation from exposure to the wide variety of circulating antigens consequent on varieties opportunistic infections in HIV patients with severe immunosuppression. 4 Our previous study indicated that most HIV patients in our setting present late with a varieties of opportunistic infections. 19 We observed good correlation between TLC and CD4 count using the Spearman's rank test (r = 0.632) in HAART-experienced and r = 0.494 in HAARTnaïve cohorts, similar to the value of 0.431 reported by Akinola.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, local resources for health care are already overstretched by HIV/AIDS and overlapping high-impact endemic diseases such as malaria, tuberculosis, and infant diarrheal illnesses. 4 Against this background, the World Health Organization (WHO) recommended the use of total lymphocyte count of less than 1.0-1.2 × 10 3 /µL in individuals with stage II or III disease as an indication to initiate antiretroviral therapy in the absence of knowing the CD4 count. 5 This recommendation was exclusively derived from studies conducted in developed countries.…”
Section: Retrovirology: Research and Treatment 2013:5 Introductionmentioning
confidence: 99%
“…CD4+ cells counts and measures of VL are surrogate biomarkers of disease progression that help to stage, initiate and monitor treatment. CD4+ cell counts provide an immunological measure of HIV progression; these counts are utilized in the care of HIV+ patients for staging infections and in assessing patients for ART eligibility [5][6][7][8]. Specialized laboratories use highly trained personnel and sophisticated flow cytometry techniques to perform CD4+ cell counts, as this is the current gold standard technique [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…CD4+ cell counts provide an immunological measure of HIV progression; these counts are utilized in the care of HIV+ patients for staging infections and in assessing patients for ART eligibility [5][6][7][8]. Specialized laboratories use highly trained personnel and sophisticated flow cytometry techniques to perform CD4+ cell counts, as this is the current gold standard technique [6,9]. When ART is available, rapid staging, continual monitoring, and retention of individuals on ART become crucial to controlling HIV infection, but the availability of quality patient monitoring in all field settings remains a challenge [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that patient care in subSaharan Africa operates under conditions where HIV quantification is frequently unsustainable for the great majority of those affected in the region resulting in a focus on CD41 T cell testing (13). In this issue, the paper by Marinucci et al reports on the experience of decentralization of CD4 testing in resource limited settings-relating 7 years of experience in six African countries.…”
mentioning
confidence: 99%